Habitat utilization patterns of wetland birds (Zoological Records and Reviews, 2024)
Wetland birds are among the most sensitive indicators of freshwater ecosystem condition, yet the fine-scale habitatfeatures determining their space use, guild-specific microhabitat selection, and foraging site fidelity are incompletelycharacterised across the gradient from natural to human-modified wetlands. This study quantified habitat utilisationpatterns for twelve wetland bird species across six functional guilds (piscivores, herbivores, probers, surface-feeders,aerial insectivores, and omnivores) at 18 wetland sites spanning natural fen, managed reedbed, restored polder, andurban stormwater pond types in Switzerland, the Netherlands, and Sweden (n = 9,284 individual detections, 2022-2023).GPS-GSM telemetry (n = 64 tagged individuals across four species) and point-count surveys were combined withvegetation structure mapping and water chemistry profiling. Resource Selection Functions (RSF) identified water depth(0.2-0.8 m), emergent vegetation cover (40-70%), and open water patch size (> 0.3 ha) as the three most consistentpositive habitat predictors across guilds (all beta > 0.42, p < 0.001). Piscivore species (Ardea cinerea, Alcedo atthis)showed the strongest selection for clear water (Secchi depth > 0.6 m; RSF beta = 0.81 and 0.74 respectively). Restoredpolder wetlands supported 68.4% of the species richness found at natural fen sites and demonstrated equivalent corehabitat quality for three of four telemetered species based on kernel density utilisation distribution (KDE95) overlapanalysis. Urban stormwater ponds supported the lowest species richness (mean 4.2 +- 1.1 species) but maintainedviable foraging habitat for Anas platyrhynchos and Fulica atra. These results provide guild-specific habitat managementtargets for restored and managed wetlands under the EU Birds Directive and Ramsar Convention obligations.